OPTICAL PROPERTIES AND ADHESIVE ABILITY OF HYBRID VIRUS NONORGANIC COMPLEXES TMV-AU - KASIYANENKO, Vasul; BURDEYNYY, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
One of the promising methods to create nanomaterials reduces to applying of viruses, whose virions, due to their high spatial symmetry, can serve as effective matrix templates that allow assembling of noble metals, in particularly Au, nanoparticles. In the connection with the above mentioned fact, it becomes interesting to investigate physical properties of materials synthesized by virus involving technology, depending on the determined virus-matrix. This paper presents some results of the study of optical and adhesive properties of gold nanoparticles in complexes with the tobacco mosaic virus